The Role of Epigenetic Mechanisms in the Treatment of GI Cancers - Shahini, Ali; Imani, Amirhossein; Reyhani, Amirali; Khalili-Tanha, Ghazaleh; Ghorbani, Elnaz; Fiuji, Hamid; Al-Hayawi, Ibrahim Saeed; Khazaei, Majid; Hassanian, Seyed Mahdi; Ferns, Gordon A; Nazari, Elham; Avan, Amir (Current Cancer Drug Targets, 2025)
Epigenetic mechanisms have been shown to play a critical role in the development and progression of gastrointestinal [GI] cancers. These mechanisms involve modifications to DNA and histones that can alter gene expression patterns and may contribute to the initiation and progression of cancers. In recent years, epigenetic therapies have emerged as a promising approach to treating GI cancers. These therapies target specific epigenetic modifications, such as DNA methylation and histone acetylation, to restore normal gene expression patterns and inhibit cancer cell growth. Several epigenetic drugs have been approved for the treatment of GI cancers. Moreover, the use of epigenetic therapies in combination with other treatments, such as chemotherapeutic agents, is being studied to improve treatment outcomes.We have provided an overview of the role of epigenetic mechanisms in GI cancer treatment aimed to focus on recent evidence of the use of epigenetic agents in clinical and preclinical GI cancer studies, including gastric, esophageal, hepatic, pancreatic, and colorectal cancers. Overall, the role of epigenetic mechanisms in GI cancer treatments is an active area of research with the potential to improve patients' treatment outcomes and advance cancer treatment strategies.
Keywords: treatment